A new first-order mixed beam element for static bending analysis of functionally graded graphene oxide powder-reinforced composite beams. (February 2022) - Vinh, Pham Van; Son, Le Truong
Abstract: In this paper, a new first-order mixed beam element is established and applied to investigate the static bending of the functionally graded graphene oxide powder-reinforced composite beams. The proposed beam element is developed via a mixed finite element formulation based on first-order shear deformation theory. The new element consists of two nodes and three degrees of freedom per node. In addition, the present beam element uses linear shape functions. The proposed beam element is free of shear locking without using selective or reduced integration. The comparison study demonstrates that the present beam element can predict exact solutions with very few elements, so, the computation cost is reduced. Then the proposed beam element is used to analyze the static bending of functionally graded graphene oxide powder-reinforced composite beams. A comprehensive parameter study is carried out to demonstrate the effects of some parameters such as the boundary conditions, graphene oxide powder weight fraction, graphene distribution patterns, graphene oxide powder dimensions, and the slender ratio of the beams.